(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This guide provides an interpretation of the EU's Rural Development Programme for 2007-13, but the legally binding basis for the EU's rural development policies and programmes are te relevant EC regulations. Policy-makers and stakeholders interested in rural development in general and land consolidation activities in particular should identify the challenges facing them and formulate appropriate policy interventions to meet those challenges through the proper communication channels with the EU member states, land consolidation should be included in their Rural Development Programme for 2007-13.
Keywords: Rural development,Consolidation of land holdings,Land tenure,Phát triển nông thôn,Sở hữu đất đai,Quyền sử dụng đất; European Union countries,European Union countries,European Union countries,Các nước Liên minh châu Âu,Các nước Liên minh châu Âu,Các nước Liên minh châu Âu